2001
DOI: 10.1055/s-0037-1615610
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of Ionic and Non-ionic Contrast Media in Nonhuman Primates

Abstract: SummaryThromboembolic complications have been attributed to the use of radiographic contrast media (CM) during interventional procedures for arterial revascularization. However, due to the low frequency of adverse events, comparisons between different CM have been difficult to perform, although it has been suggested that ionic (vs. non-ionic) CM may be associated with fewer thrombotic events. The present study was undertaken using well-characterized baboon thrombosis models in order to compare different CM und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Nonionic low-osmolar IRCMs and isosmolal iodixanol permit greater thrombin generation and platelet and fibrin deposition in animal models 3943 than ionic ioxaglate. Increased local thrombus formation during coronary intervention in humans occurs with nonionic compared with ionic low-osmolar contrast material.…”
Section: Discussionmentioning
confidence: 99%
“…Nonionic low-osmolar IRCMs and isosmolal iodixanol permit greater thrombin generation and platelet and fibrin deposition in animal models 3943 than ionic ioxaglate. Increased local thrombus formation during coronary intervention in humans occurs with nonionic compared with ionic low-osmolar contrast material.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro model by Corot et al demonstrated increased thrombin time with ioxaglate, iohexol, and iodixanol compared to saline controls . Similarly, in a baboon thrombosis model, all three agents were inherently antithrombotic compared to stents infused with saline . However, in these studies, ioxaglate was associated with a thrombin time more than five times that with iodixanol.…”
Section: Discussionmentioning
confidence: 94%
“…However, in these studies, ioxaglate was associated with a thrombin time more than five times that with iodixanol. Ioxaglate was also associated with a lower amount of fibrin deposition on stents compared with iohexol, which in turn was associated with a lower amount of fibrin deposition than iodixanol . In an in vitro model conducted by Jones et al, no thrombi were formed when blood was mixed with ioxaglate, while thrombi formed with iohexol weighed less than those formed with iodixanol .…”
Section: Discussionmentioning
confidence: 97%
“…The loss of plasma proteins would result in the decrease of whole blood viscosity. (3) contrast media was reported to decrease the erythrocyte aggregation in vivo [1,4,10], which would decrease the whole blood viscosity.…”
Section: Discussionmentioning
confidence: 99%